2021
DOI: 10.1111/ajt.16801
|View full text |Cite
|
Sign up to set email alerts
|

Transplant trends in Mexico during the COVID-19 pandemic: Disparities within healthcare sectors

Abstract: Healthcare systems worldwide were challenged during the COVID‐19 pandemic. In Mexico, the public hospitals that perform most transplants were adapted to provide care for COVID‐19 patients. Using a nationwide database, we describe the first report of the impact of COVID‐19 and related transplantation healthcare policies in a middle‐income country by comparing statistics before and during the pandemic (pre‐COVID: March 2019–February 2020 vs. COVID era: March 2020–February 2021) and by type of institution (public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
0
13
0
2
Order By: Relevance
“…10 A Mexican study also found that transplants decreased more in public institutions than in private institutions (89% vs 57%). 11 COVID-19 has also negatively affected transplantation activities in general (public) transplantation centres in India. 12…”
Section: Discussionmentioning
confidence: 99%
“…10 A Mexican study also found that transplants decreased more in public institutions than in private institutions (89% vs 57%). 11 COVID-19 has also negatively affected transplantation activities in general (public) transplantation centres in India. 12…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in transplants became more prominent for patients with public insurance than private insurance. Another study from Mexico showed an unequal reduction of liver transplantation for public (88% reduction) and private (35% reduction) hospitals during the COVID-19 pandemic[ 82 ].…”
Section: Liver Transplantationmentioning
confidence: 99%
“…2,5,6 Aside from increased morbidity and mortality of vulnerable populations caused directly by COVID-19, adverse effects caused by the pandemic permeate into morbidity and mortality in other areas of medicine on these vulnerable populations as well due to disparities in underlying healthcare infrastructure and resource allocation. 7 In addition, many people experienced increased socioeconomic risks during the COVID-19 pandemic, including food insecurity, housing instability, transportation difficulties, and utilities difficulties. 8 Similar to the multifactorial nature of disparities related to COVID-19, multifactorial healthcare disparities in orthopedic care also exist.…”
Section: Introductionmentioning
confidence: 99%